Gestión de Proyectos Ágil Con Scrum - SI666 - 202101 - Cobeñas Sanchez, Rosa America (2021)
Elective specialty course in Agile Project Management with Scrum, in the Software Engineering career and of a theoretical-practical nature aimed at students of the eighth cycle. The course corresponds to the area of training in project management and work teams, being on a theoretical- practical nature with greater emphasis on the practical part. Purpose: Its main objective is to manage a project with scrum and participate in "agile teams" and to develop the management, communication, and collaboration skills necessary for the development of projects, as well as to emphasize the soft skills necessary to work in an agile environment. The course contributes to the development of general competence Innovative thinking and the competence 2 ABET: "An ability to apply engineering design to produce solutions that meet specified needs with consideration of public health, safety, and welfare, as well as global, cultural, social, environmental, and economic factors"